Chemical Composition, Antioxidant and Antibacterial Properties of Essential Oil from Ocotea Auriculiformis Kost. (Lauraceae) Leaves, Endemic of Madagascar - Rigobert, Andrianantenaina; Rahanira, Ralambondrahety; Onja, Andriambeloson; Delphin, Rabehaja; Laurence, Ralamboranto; Rado, Rasolomampianina (European Scientific Journal, ESJ, 2017)
Plants constitute an important source of secondary metabolites in which essential oils are well-known for their use in various domains such as pharmacy, therapeutic, cosmetology and foods. In vitro antimicrobial and antioxidant properties of Ocotea auriculiformis Kost. (Lauraceae) leaves essential oil is demonstrated and its chemical composition is reported in the present study. The essential oil from Ocotea auriculiformis Kost. (Lauraceae) leaves, an endemic plant of Madagascar was extracted by hydrodistillation method. Chemical composition using GC, GC/ MS and NMR13C methods showed that the essential oil contained around 47 products in which 93.95% were identified. Known compounds are constituted by 74.7% of hydrocarbons and 19.25% of oxygenated products. The essential oil is rich in sesquiterpene and monoterpene. In vitro antibacterial capacity of the essential oil was assessed by disc method against human and food pathogens. Bacillus cereus and Streptococcus pneumoniae were very sensitive to the essential oil with 11 mm and 25 mm of inhibition zone respectively. The MIC of the essential oil was 1mg/mL for Bacillus cereus and 0.25 mg/mL for Streptococcus pneumoniae. MBC values were 2.5 mg/mL and 0.5 mg/mL, respectively. The ratio MBC/MIC for both strains was inferior to 4 concluding hence that the essential oil has bactericidal effect against the two sensitive strains. In vitro antioxidant capacity of the essential oil was performed according to qualitalive (TLC) and quantitative (measure of DPPH radical scavengening) methods. The essential oil showed antioxidant activity with IC50 value of 0.35 mg/mL.